Country Risk Effects and Government Domestic Debt Nexus in South Africa - Habanabakize, Thomas; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2023)
Country risk rating is one of the factors that determine the stability of a given country’s economy and the government’s access to both domestic and foreign loans. This paper aimed at assessing the relationship that exists between country risk rating and the South African government’s access to domestic debts or loans. Monthly data from January 2008 to December 2019 was investigated using the ARDL bounds testing approach and the error correction model (ECM). The findings of this paper indicated that all country risk components (economic, financial and political) have a significant long-run effect on government domestic debt. While economic and financial risk scores have a positive effect on government debts, an inverse relationship was found between political risk and government debt. These results imply that in order to be independent of foreign debt which comes with terms and conditions; policymakers and the South African government leaders should strive to sustain the stability of the economy and the country’s financial conditions.